AMYOTROPHIC LATERAL SCLEROSIS (ALS) IN GEORGE COSTELLA WOLFE’S YOU ARE NOT YOU (SOCIOLOGICAL APPROACH) - Haerani Haerani (Elite : English and Literature Journal, 2017)
AbstractThis thesis studied about Amyotrophic Lateral Sclerosis (ALS) based on the script of the movie You Are Not You which was released in 2014. This research aimed to describe and analyze the ways to heal and cure the ALS disease and how the main character’s social life during facing this disease in the movie. This research focused on sociological approach and based on the theory of Amyotrophic Lateral Sclerosis (ALS) by National Institute of Health (NIH) theory. This research used descriptive qualitative method and used note taking as the instrument. The findings showed that there are twenty-three data from six ways to heal and to cure the disease, they are: two therapies from Physicians, four therapies from Pharmacists, one physical treatment, two occupational and speech therapies, two therapies from nutritionist and twelve therapies from social workers and home care and hospice nurse. Meanwhile, there are eight social interactions by Kate with other character (individual to individual) and there are six social interactions by Kate with more than one character (individual to group).AbstrakPenelitian ini tentang penyakit Amyotrophic Lateral Sclerosis (ALS) berdasarkan skrip pada film You Are Not You yang ditayangkan pertama kali pada tahun 2012. Penelitian ini bertujuan untuk menjelaskan dan menganalisis cara mengobati penyakit ALS dan bagaimana kehidupan sosial si penderita penyakit dalam film tersebut. Penelitian ini menggunakan pendekatan sosiologi dan berdasarkan teori Amyotrophic Lateral Sclerosis (ALS) oleh National Institute of Health (NIH). Penelitian ini menggunakan metode deskriptif kualitatif dengan instrumen note taking. Penelitian ini menemukan dua puluh tiga data dari enam cara mengobati penyakit ALS yaitu melalui dua terapi dari dokter, empat terapi dari apoteker, satu terapi fisik, dua terapi peralatan dan terapi wicara, dua terapi diet dan dua belas terapi oleh perawat di rumah. Sementara, ada delapan interaksi individu dan enam interaksi kelompok yang dilakukan oleh Kate selama menghadapi penyakit ini.